Quality Evaluation by Fourier Transform Infrared Spectroscopy the Avocado Oil’s the Varieties Hass, Criollo and Fuerte - Méndez, Úrsula Irene Ortega; Quintero, Juan Emilio Ariza; Ortega, Tito Emilio Ariza; Ortega, Argelia Ariza; Ortega, José Alberto Ariza; Ortega, Ulises Ariza (Chemical and Materials Sciences: Research Findings Vol. 3, 2025)
The Mexican avocado is a fruit recognized worldwide level due to the high quality of its nutrients. The main problem of the producers is the short time of maturation and oxidation that presents this fruit because it has been demonstrated that the visual appearance of a product is the first impact that takes the consumer to acquire it. The avocado in Mexico has begun to industrialize in products such as paste and oil. Edible oils are obtained by two procedures by pressing the fruit and with organic solvents. However, there are reports that indicate that the use of solvents affects the quality of the fatty acids inducing the formation of trans isomers, which are banned in many countries as they can cause cardiovascular diseases and increase cholesterol when consumed in large quantities. The purpose of this work was to evaluate by Fourier transform infrared spectroscopy (FTIR) the avocado oils of the varieties Hass, Criollo and Fuerte extracted by centrifugation (AHC, AFC and ACC, respectively) and with hexane (AHH, ACH and AFH, respectively) to determine its quality. The oil’s evaluation was obtained by FTIR in the mid-region (600-4000 cm-1). The Hass avocado oils were extracted by centrifugation and solvent methods. Transform Infrared Spectrometer (FTIR Bruker Vertex-70) was used in the measurement mode called Attenuated Total Reflectance (ATR). The AHC, AFC and ACC oil’s FTIR spectra show a very intense band at the frequency 723 cm-1, which corresponds to the functional group cis with a bending vibration mode. For the AFH the trans functional group was identified in the band sited at 968 cm-1 with a strong intensity. The centrifuge method is an alternative for obtaining avocado oil because the degradation of the fatty acids is minimal and the green color is maintained. The sample that shows a higher concentration of trans was the Fuerte variety Avocado oil extracted by Hexane solvent.